Sequence Analysis of SSR-Flanking Regions Identifies Genome Affinities between Pasture Grass Fungal Endophyte Taxa. (20th December 2010) - van Zijll de Jong, Eline; Guthridge, Kathryn M.; Spangenberg, German C.; Forster, John W.
Abstract : Fungal species of the Neotyphodium and Epichloë genera are endophytes of pasture grasses showing complex differences of life-cycle and genetic architecture. Simple sequence repeat (SSR) markers have been developed from endophyte-derived expressed sequence tag (EST) collections. Although SSR array size polymorphisms are appropriate for phenetic analysis to distinguish between taxa, the capacity to resolve phylogenetic relationships is limited by both homoplasy and heteroploidy effects. In contrast, nonrepetitive sequence regions that flank SSRs have been effectively implemented in this study to demonstrate a common evolutionary origin of grass fungal endophytes. Consistent patterns of relationships between specific taxa were apparent across multiple target loci, confirming previous studies of genome evolution based on variation of individual genes. Evidence was obtained for the definition of endophyte taxa not only through genomic affinities but also by relative gene content. Results were compatible with the current view that some asexual Neotyphodium species arose following interspecific hybridisation between sexual Epichloë ancestors. Phylogenetic analysis of SSR-flanking regions, in combination with the results of previous studies with other EST-derived SSR markers, further permitted characterisation of Neotyphodium isolates that could not be assigned to known taxa on the basis of morphological characteristics.